ANALISIS BAURAN PEMASARAN, RISIKO, DAN KINERJA KEUANGAN AGROINDUSTRI KOPI BUBUK CAP OBOR MAS LAMPUNG, DI KECAMATAN KOTABUMI KOTA, KABUPATEN LAMPUNG UTARA - Akbar, Tegar Ramadhan; Lestari, Dyah Aring Hepiana; Nugraha, Adia (Lampung University, 2020)
This research aims to analyze marketing mix that consists of agroindustry?s owner and coffee powder consumer pespective, agroindustry risk, risk management of ISO 31000: 2009, and financial ratio of agroindustry. This research is a case study method at coffee powder agroindustry in Kotabumi City Sub-District, North Lampung Regency. Data of this research were collected in December 2018 until February 2019. The results show that marketing strategy of agroindustry has used the 7P marketing mix component, which the product, place, price, process, people,and physical evidence are good, while for the promotion component, it has not been used optimally. Agroindustry risk consisting of production risk, price risk, and income risk shows the low value of risk. Agroindustry has well applied Management Risk of ISO 31000: 2009 which is based on operational risk that consist of process risk, people risk, and incidental risk. Financial ratio consisting of current ratio, debt to equity ratio, total asset turn over, and net profit margin shows a bad financial performance in 3 years production.Key words: agroindustry, coffee powder, financial ratio, marketing mix, risk